Symbolic “Iconic Sites” vs. “Quotidian Worlds”—industrial landscapes in 1960s Polish cinema - Copik, Ilona (Polskie Studia Krajobrazowe, 2019)
This paper examines industrial landscapes in Polish Cinema in the 60s. Upper Silesian scenery is considered not as a mere background but an essential element that constructs the cinematographic narration. Historic, economic, and socio-cultural context is brought up to draw attention to the propagandizing role of cinema in the 60s. The category of “iconic sites” proposed by Tim Edensor is introduced to analyze cinematographic depictions of Upper Silesia. Movies show the processes of industrialization framed by the strict artistic rules proposed by the Polish People Republic’s officials. The analyzed examples show the adoption of a distanced outsider’s perspective that is based on geographical and cultural orientation points. The propaganda images seen as “iconic sites” are confronted with another interpretative category proposed by Edensor, “quotidian worlds,” constituted by products of grassroots practices, focused on capturing the space of everyday experiences (surroundings) from the perspective of a citizen.